Advancements in fire-related toxic gas detection and prophylactic strategies: A focus on cyanide concentration analysis and antidote efficacy in controlled smoke inhalation models - Jowy Tani; Jia-Long Chen; Wei-Chuan Liao; Chia-Hung Chen; Chau-Hui Wang; Tzu-hui Sun; Yow-Ling Shiue; Jin-Wu Tsai (PLoS ONE, 2026)
Fire smoke inhalation represents a major cause of acute mortality in fire incidents, with hydrogen cyanide being a critical contributor to rapid systemic toxicity. This study aimed to establish a controlled smoke inhalation model to characterize cyanide-dominant exposure and to evaluate the prophylactic efficacy of a nebulized antidote combination under acute conditions. A reproducible smoke chamber system was developed to generate cyanide-rich toxic atmospheres. C57BL/6 mice were exposed to controlled cyanide concentrations, followed by prophylactic administration of a nebulized formulation containing hydroxocobalamin and deferoxamine. Survival outcomes were assessed to evaluate the protective effects of the intervention. Controlled cyanide exposure resulted in rapid and dose-dependent lethality. Prophylactic inhalation of the nebulized antidote significantly improved short-term survival compared with untreated controls ( p < 0.05), consistent with effective mitigation of cyanide toxicity. In conclusion, this study establishes a reproducible cyanide-focused smoke inhalation model and provides experimental evidence supporting the potential of aerosolized hydroxocobalamin-based prophylaxis as an immediate protective strategy during fire smoke exposure. These findings support the feasibility of rapid, non-invasive intervention aimed at preserving a critical time window for escape and subsequent medical treatment in fire-related emergencies.